Pemanfaatan Algoritma FP-Growth Untuk Menentukan Strategi Penjualan Pada Kedai Kopi Teras Garden - Adrian Marvel Ugrasena; Achmad Zakki Falani (Systemic: Information System and Informatics Journal, 2020)
Data mining is a process extracting data from the dataset. In this paper will try to apply data mining on data transaction in Kedai Kopi Teras Garden for sales strategy by creating recommendation item that suit to be sold by package system or the other words by to be sold simultaneously. This paper use association rule method with fp-growth algorithm to find customer purchase pattern on Kedai Kopi Teras Garden. The output of this paper will create some rules for recommendation item that can be sold as a package according to data that already collected and processed with association rule method. Data will be divided by 2, dry season data and rainy season data because there’s customer pattern change accordingly with the season.